FPGA implementation of modified PAPR reduction technique for OOFDM system - N. Kareem, Ali; M. Abdul Satar, Sinan; A. Husein, Mohammed (International Journal of Engineering and Technology, 2019)
Orthogonal Frequency Division Multiplexing (OFDM) has been widely adopted in optical communication systems. However, the Peak-to-Average Power Ratio (PAPR) is considered one of the major drawback factors of communication system, so various methods have been proposed to reduce this factor. The modified logarithmic companding technique is used for reducing this factor in current paper. In addition, the main goal of this paper is the field-programmable gate array (FPGA) implementation of this modified companding technique. The software package called LabVIEW is used for programming the FPGA hardware. All results of Quality Factor (QF), Bit Error Rate (BER) and constellation diagram have been presented by combining the VPI Transmission Maker, MATLAB, LabView, and FPGA hardware. That is to say, the proposed implementation of the modified companding can offer a better PAPR reduction, BER, and QF at control parameter y at 0.1. To put it another way, the PAPR is reduced by 6.2 dB at 1×10-3 Complementary Cumulative Distribution Function (CCDF). Accordingly, getting 3.8 dB improvement of QF in comparison with the original system and the BER is 4.8×10-5.
Keywords: Orthogonal Frequency Division Multiplexing (OFDM); Field-Programmable Gate Array (FPGA); Peak-to-Average Power Ratio (PAPR); Quality Factor (QF); Bit Error Rate (BER).